Communicative relevance: Color references in bilingual and trilingual speakers - Pavlenko, Aneta; Jarvis, Scott; Melnyk, Svitlana; Sorokina, Anastasia (Bilingualism: Language and Cognition, 2017)
The study examined granularity of lexical partitioning of the blue area in speakers of English, which encodes the term blue; Russian, which encodes two terms, sinij [dark/navy blue] and goluboj [light/sky blue]; and Ukrainian, which encodes the terms synij [dark/navy blue] and blakytnyj and golubyj [light/sky blue]. Five groups of participants took part in the study: (1) 30 L1 speakers of English, (2) 30 L1 speakers of Russian, (3) 30 Russian–English bilinguals, (4) 30 English–Russian bilinguals, and (5) 25 Ukrainian–Russian–English trilinguals. Quantitative and qualitative analyses revealed that L1 Russian speakers referred to different types of blue significantly more frequently than all other groups, while bilinguals patterned with L1 English speakers. These findings suggest that classroom exposure to L2 Russian does not make the distinction between sinij and goluboj communicatively relevant for L1 English speakers and that everyday use of L2 English may trigger attrition of the contrast in L1 Russian.
Keywords: Russian; bilingual lexicon; color; communicative relevance; crosslinguistic influence; dept.wll

Crimean crisis of 2014 in the conservative and liberal U.S. media - Sorokina, Anastasia N. (Russian Journal of Communication, 2017)
Keywords: Crimean crisis; U.S. media; critical discourse analysis; dept.wll; transitivity

Inclusive pedagogy for English language learners: A handbook of research-informed practices - Verplaetse, Lorrie Stoops; Migliacci, Naomi (Routledge, 2017)
In this Handbook leading researchers, teacher educators, and expert practitioners speak to current and future educators and educational leaders in understandable language about the research that informs best practices for English language learners integrated into the K-12 public school system. Responding to current state and federal mandates that require educators to link their practices to sound research results, it is designed to help educators to define, select, and defend realistic educational practices that include and serve well their English language learning student populations. A critical and distinctive feature of this volume is its non-technical language that is accessible to general educators who have not been trained in the fields of second-language development and applied linguistics. Each chapter begins with a thorough discussion of the recommended practices, followed by a description of the research that supports these practices. The rigor of reported research is contained, but this research is written in a lay person’s terminology, accompanied by bibliographies for readers who wish to read about the research in technical detail. The volume is structured around four themes:• In the Elementary Classroom• In the Middle and Secondary Classroom• School and Community Collaboration• School and District Reform. Inclusive Pedagogy for English Language Learners is intended for current and future educational administrators, all educators who have a keen interest in school reform at the classroom, school, or district level, and staff developers, policy makers, parents and community groups, and anyone interested in the successful education of linguistically and culturally diverse students.
Keywords: dept.wll

Emerging second language writing identity and complex dynamic writing - Tu, I-Ju (Journal of World Languages, 2017)
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00378
Keywords: dept.wll

Review of 'Ethics of life: contemporary Iberian debates' - Flores, William (Hispania-a Journal Devoted to the Teaching of Spanish and Portuguese, 2017)
0 citations (Crossref) [2023-10-31] tex.eissn: 2153-6414 tex.unique-id: ISI:000411169300014
Keywords: dept.wll; peer-reviewed

Soldier-poet or écrivain-combattant: How the French trenches of World War I defined witnessing - Gleisner, Nichole T. (Studies in 20th & 21st Century Literature, 2017)
0 citations (Crossref) [2023-10-31]
Keywords: dept.wll

Patterns of tasks, patterns of talk: L2 literacy building in university Spanish classes - Gleason, Jesse; Slater, Tammy (Language, Culture and Curriculum, 2017)
Second language (L2) classroom research has sought to shed light on the processes and practices that develop L2 learners' abilities [Nunan, D. 2004. Task-based language teaching. London: Continuum; Verplaetse, L. 2014. Using big questions to apprentice students into language-rich classroom practices. TESOL Quarterly, 179, 632-641; Zeungler, J., & Mori, J. 2002. Microanalyses of classroom discourse: A critical consideration of method. Applied Linguistics, 23(3), 283-288]. Honing in on the micro-level of classroom tasks and even further into the language of the tasks can help to reveal the patterns in teacher- and student-talk that help scaffold students' academic literacy. Literacy, from a systemic functional view of language learning, entails having the tools to function in the social contexts that are valued in students' lives. This study illustrates how grounded ethnography was used in conjunction with functional discourse analysis to illuminate bi-literacy development in two third-year university Spanish writing classes. Findings uncovered unique patterns of tasks and oral interactions that helped build students' academic bi-literacy. While grammar tasks helped build students' knowledge of wording-meaning relationships, culture and writing tasks supported their evolving understanding of how language construes content. This study puts forth a systemic functional curricular model for literacy-based tasks that aims to bridge the previously observed language-content gap.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/037-343-356-989-268, pop00144 tex.type: [object Object]
Keywords: Language learning tasks; academic literacy; blended learning; classroom discourse; dept.wll; systemic functional linguistics; third-year Spanish courses

Ghost returns and historical memories in Zhang Yimou's Gui lai and Pedro Almodóvar's Volver - Weng, Miaowei (Canadian Review of Comparative Literature / Revue Canadienne de Littérature Comparée, 2017)
0 citations (Crossref) [2023-10-31]
Keywords: dept.wll

Book Review: The labor of literature: democracy and literary culture in modern Chile. by Jane D. Griffin. Amherst and Boston: U of Massachusetts p, 2016, p. 218, 25.95/85.00. - Cardone, Resha Sophia (The Latin Americanist, 2017)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/015-933-729-134-257 tex.type: [object Object]
Keywords: book.review; dept.wll

Poesía concreto: Vuelta o la ciudad de México petrificada - Hernandez, Rafael (Revista Boletín Redipe, 2017)
Citation Key Alias: lens.org/151-184-573-755-051
Keywords: dept.wll; ⛔ No DOI found

La magia del amor, los horrores de la muerte y otros temas en los cuentos de Gabriel García Márquez - Pelayo, Ruben (Revista Boletín Redipe, 2017)
Citation Key Alias: lens.org/142-405-989-156-247
Keywords: dept.wll; ⛔ No DOI found